1992
DOI: 10.1007/bf01974018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of HLö-7 and pyrimidoxime as antidotes of nerve agent poisoning in mice

Abstract: The toxicity and efficacy of two oximes, HLö-7 and pyrimidoxime, were evaluated in mice and compared to those obtained with HI-6. HLö-7 and pyrimidoxime produced 24 h LD50 values of 356 and 291 mg/kg (i.p.), respectively. In combination with atropine (17.4 mg/kg, i.p.), HLö-7 was a very efficient therapy against poisoning by 3 x LD50 dose of soman, sarin and GF and 2 x LD50 dose of tabun with ED50 values of 12.4, 0.31, 0.32 and 25.2 mg/kg, respectively. In contrast, pyrimidoxime was a relatively poor therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…The prophylactic administration of antidotes was used because this procedure is suitable for a mechanistic study that compares the reactivating efficacy of various oximes. The technique should give better results than the treatment of animals after poisoning and reduce the influence of aging of the nerve agent-AChE complex [16]. Moreover, some oximes are planned to be used prophylactically in certain chemical warfare scenarios [9].…”
Section: Methodsmentioning
confidence: 99%
“…The prophylactic administration of antidotes was used because this procedure is suitable for a mechanistic study that compares the reactivating efficacy of various oximes. The technique should give better results than the treatment of animals after poisoning and reduce the influence of aging of the nerve agent-AChE complex [16]. Moreover, some oximes are planned to be used prophylactically in certain chemical warfare scenarios [9].…”
Section: Methodsmentioning
confidence: 99%
“…135 It was found that HLö-7 induced a significant reactivation of AChE in mice diaphragms previously inhibited with tabun, sarin, soman and cyclosarin. 136 Although both HI-6 and HLö-7 can antagonize sarin-induced hypothermia (thus proving that they can pass the blood-brain barrier and gain access to the CNS when given with atropine), 136,137 the LD 50 of HLö-7 is 2.5 times less than that of HI-6, indicating the higher per se toxicity of the newer oxime. 136 The cardiovascular tolerability of HLö-7 was close, but still not as good as HI-6, at least in anesthetized guinea pigs.…”
Section: Drawbacks and Limitations Of Oxime Therapymentioning
confidence: 99%
“…136 Although both HI-6 and HLö-7 can antagonize sarin-induced hypothermia (thus proving that they can pass the blood-brain barrier and gain access to the CNS when given with atropine), 136,137 the LD 50 of HLö-7 is 2.5 times less than that of HI-6, indicating the higher per se toxicity of the newer oxime. 136 The cardiovascular tolerability of HLö-7 was close, but still not as good as HI-6, at least in anesthetized guinea pigs. 138 On the scale of efficacy, HLö-7 turned out to be somewhat more effective than HI-6 against tabun and VX poisoning and less effective against sarin and soman, as well as cyclosarin intoxication.…”
Section: Drawbacks and Limitations Of Oxime Therapymentioning
confidence: 99%
“…These promising results highlighted HLö-7 as a very broad spectrum oxime reactivator. 34 The problem of solubility in water and relative instability was solved by preparationof HLö-7 dimethanesulfonate salt ( …”
Section: History and Physico-chemical Properties Of Hl ö-7mentioning
confidence: 99%